2020
DOI: 10.1186/s12891-020-3188-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing the effectiveness of surgical and nonsurgical treatment for cervical radiculopathy

Abstract: Background: Cervical radiculopathy is usually caused by disc herniation or spondylosis. The prognosis is expected to be good in most patients, but there is limited scientific evidence on the indications for nonsurgical and surgical treatments. The aim of the present study is to evaluate and compare the effectiveness of surgical and nonsurgical treatment in two trialsincluding disc herniation and spondylosis, respectively, and to evaluate factors that contribute to better decision making. Methods/design: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Cervical radiculopathy is usually caused by cervical disc herniation, spondylosis or a combination of herniation and spondylosis which may trigger local ischaemia and inflammation [ 14 ]. Recent studies have demonstrated a favourable natural course of CSR within the first 4–6 months with complete recovery ranging from 24 to 36 months in approximately 83% of patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical radiculopathy is usually caused by cervical disc herniation, spondylosis or a combination of herniation and spondylosis which may trigger local ischaemia and inflammation [ 14 ]. Recent studies have demonstrated a favourable natural course of CSR within the first 4–6 months with complete recovery ranging from 24 to 36 months in approximately 83% of patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic degeneration of the cervical spine is the basic cause of the occurrence and development of CSR. The main symptoms of CSR are neck pain, arm numbness, and limited neck movement, and some patients with CSR develop depression and insomnia, which seriously decrease quality of life [ 2 ]. For CSR that does not respond to conservative treatment, anterior cervical decompression and fusion (ACDF) is a routine and effective method that is considered the “gold standard” [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many nondrug conservative treatment methods, such as acupuncture, massage, herbal compresses, low frequency therapy, and microwaves, all of which are effective. Numerous studies have shown that the clinical efficacy of conservative treatment and surgical treatment is the identical [3] . Therefore, it is important to investigate how best combined conservative treatment can be used to improve neck pain and nerve root symptoms in patients with radiculopathy and to alleviate the progression of cervical spondylosis.…”
Section: Introductionmentioning
confidence: 99%